Short‐term melatonin consumption protects the heart of obese rats independent of body weight change and visceral adiposity. Issue 3 (20th September 2014) - Nduhirabandi, Frederic; Huisamen, Barbara; Strijdom, Hans; Blackhurst, Dee; Lochner, Amanda
Abstract Chronic melatonin treatment has been shown to prevent the harmful effects of diet‐induced obesity and reduce myocardial susceptibility to ischaemia‐reperfusion injury (IRI). However, the exact mechanism whereby it exerts its beneficial actions on the heart in obesity/insulin resistance remains unknown. Herein, we investigated the effects of relatively short‐term melatonin treatment on the heart in a rat model of diet‐induced obesity. Control and diet‐induced obese Wistar rats (fed a high calorie diet for 20 wk) were each subdivided into three groups receiving drinking water with or without melatonin (4 mg/kg/day) for the last 6 or 3 wk of experimentation. A number of isolated hearts were perfused in the working mode, subjected to regional or global ischaemia‐reperfusion; others were nonperfused. Metabolic parameters, myocardial infarct sizes (IFS), baseline and postischaemic activation of PKB/Akt, ERK42/44, GSK‐3β and STAT‐3 were determined. Diet‐induced obesity caused increases in body weight gain, visceral adiposity, fasting blood glucose, serum insulin and triglyceride (TG) levels with a concomitant cardiac hypertrophy, large postischaemic myocardial IFSs and a reduced cardiac output. Melatonin treatment (3 and 6 wk) decreased serum insulin levels and the HOMA index (P < 0.05) with no effect on weight gain (after 3 wk), visceral adiposity, serum TG and glucose levels. It increased serum adiponectin levels, reduced myocardial IFSs in both groups and activated baseline myocardial STAT‐3 and PKB/Akt, ERK42/44 and GSK‐3β during reperfusion. Overall, short‐term melatonin administration to obese/insulin resistant rats reduced insulin resistance and protected the heart against ex vivo myocardial IRI independently of body weight change and visceral adiposity.